Gait Analysis Method Focused on Skeleton Pose Estimation Using Wheeled Gait-Training Walker - Hidehisa Nakayama; Kazutoshi Ogawa; Tsugito Maruyama (Journal of Systemics, Cybernetics and Informatics)

(untitled)
We studied a gait analysis method focusing on skeleton pose estimation based on videos taken during gait-training with a wheeled walker for a person with a case history. For skeleton pose estimation, OpenPose was used. Thirteen gait parameters were designed from the extracted keypoints considering the opinions of some rehabilitation staff. As a result, we found a correlation between the load balance of a left-right elbow and the stability of a left-right posture. This suggests that the stability of walking can be evaluated by training with our developed wheeled walker